2020
DOI: 10.3389/fpls.2019.01647
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Bloom Time in Low Chilling Sweet Cherry (Prunus avium L.) Using a Multi-Family QTL Approach

Abstract: Bloom time in sweet cherry (Prunus avium L.) is a highly heritable trait that varies between genotypes and depends on the environmental conditions. Bud-break occurs after chill and heat requirements of each genotype are fulfilled, and dormancy is released. Bloom time is a critical trait for fruit production as matching cultivar adaptation to the growing area is essential for adequate fruit set. Additionally, low chilling cultivars are of interest to extend sweet cherry production to warmer regions, and for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 62 publications
(152 reference statements)
7
53
0
Order By: Relevance
“…QTLs were identified for bloom and maturity timing for sweet and sour cherry in the same genomic region as for peach; in sour cherry, the late-flowering alleles appear to be from the P. fruticosa sub-genome 78 . The very early bloom timing in the sweet cherry landrace “Cristobalina” associated with a very low chilling requirement was shown to be due to homozygosity for a large-effect QTL on a different chromosome that co-located with dormancy genes previously identified in peach 140 .…”
Section: Genomics and Socio-economics Knowledge Informs All Stages Ofmentioning
confidence: 81%
See 1 more Smart Citation
“…QTLs were identified for bloom and maturity timing for sweet and sour cherry in the same genomic region as for peach; in sour cherry, the late-flowering alleles appear to be from the P. fruticosa sub-genome 78 . The very early bloom timing in the sweet cherry landrace “Cristobalina” associated with a very low chilling requirement was shown to be due to homozygosity for a large-effect QTL on a different chromosome that co-located with dormancy genes previously identified in peach 140 .…”
Section: Genomics and Socio-economics Knowledge Informs All Stages Ofmentioning
confidence: 81%
“…comm.) Strawberry Perpetual flowering Validated, FaPFRU (LG4A) 115 ; sub-genome localization 116 ; DNA test validation 128 Sweet cherry Self-compatibility DNA test, S (LG6, S4, allele) 132 Cross-compatibility DNA test, S (LG6) 130 Bloom timing Discovered, (LG1) 140 Sour cherry Bloom timing Validated, (LG4) 78 Traits types are fruit quality, disease resistances, and physiological disorders, phenology, and productivity. …”
Section: Genomics and Socio-economics Knowledge Informs All Stages Ofmentioning
confidence: 99%
“…In apricot and peach, it has been observed that FD and MD also display broad variability and a large positive correlation 4,5 . Early and late blooming are also breeding objectives for market and crop adaptation 6 . In colder regions, late blooming may be desired to avoid damage due to spring freezes, and in warmer regions, low chilling requirement cultivars are desired to ensure flowering.…”
Section: Introductionmentioning
confidence: 99%
“…The use of single biparental populations for QTL analyses and mapping strategies limits QTL detection and the potential of results for marker-assisted selection in a wide range of plant materials with different genetic backgrounds. Only three studies on FS 21 , FF 24 , and BT 6 have combined a large number of individuals from multiple sweet cherry populations for QTL analysis. These works have resulted in the identification of large stable QTLs for these traits.…”
Section: Introductionmentioning
confidence: 99%
“…As global warming increases, unveiling the mechanism of flower bud dormancy and chilling requirement and the development of low-chill cultivars is of great importance for sustained production of plum. Low-chill cultivars of deciduous fruit trees have been used to identify genes related to bud domancy regulation 31,32,39,47,55,120,121 .…”
Section: Discussionmentioning
confidence: 99%